Ictiofauna y desarrollo del sector hidroeléctrico en la cuenca del río Magdalena-Cauca, Colombia (2014)
The Magdalena-Cauca River basin has 213 species of freshwater fish, of which slightly more than 50% are endemic. This basin accounts for 80% of the Colombian population, holds 80% of the national GDP and within its channels are located the 84% of the hydroelectric plants that supply energy to Colombia. The Andean mountains generate altitudinal gradients in aquatic systems as well as its associated biota along the Magdalena-Cauca basin. To analyze the interaction between the altitudinal gradient in the distribution of species of freshwater fish and the location of existing reservoirs, it was performed an analysis of the altitudinal distribution of endemic and migratory fish species and their implications for their conservation based on the current and future state in the formation of reservoirs, using a review of case studies at global and national levels. It was found that the number of species is inversely proportional to altitude, while the endemics are directly proportional and reservoirs below 700 m altitude affect the conservation status of migratory species. A reservoir creates new species richness gradients and modifies the channels that are used by migratory species as spawning areas. We conclude that the development of the hydropower based on the use of water in the Andean rivers and another activities associated with economic development of Colombian society, has led to changes in freshwater aquatic systems in the Magdalena-Cauca basin, influences in the structure of the assemblages of species of fish and in the dynamic of migration and spawning of freshwater fish species important for artisanal fisheries.